Ganyong-kelor snack bar's glycemic index as a diet for diabetics - Diyan Yunanto Setyaji; Fransisca Shinta Maharini (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2021)
Background: Lack of insulin or the inability of cells to respond to insulin causes high blood glucose levels or hyperglycemia, a hallmark of diabetes. Consumption of foods with a low glycemic index and high fiber has been shown to provide the same benefits as pharmacological therapy in the control of postprandial hyperglycemia and can prevent the incidence of hypoglycemia in people with diabetes. Ganyong (Canna edulis) is a food source of carbohydrates and fiber. Kelor (Moringa oliefera) contains protein and some phytochemical compounds which have a hypoglycemic effect.Objectives: The objective of the study was to analyze the glycemic index of ganyong-kelor snack bars as a diet for diabetics.Materials and Methods: Ten respondents fasted for 10 hours and checked their fasting blood glucose levels, then consumed 105 grams of bread as the reference food. Every 30 minutes after eating, the blood glucose levels were checked. In the following week, after fasted, all respondents consumed 157 grams of a ganyong-kelor snack bar and checked their blood glucose levels every 30 minutes.Results: Every 100 grams of ganyong-kelor snack bar contains 230.13 kcal, 31.97 grams of carbohydrates, 9.25 grams of fat, and 4.75 grams of protein. In this study, bread was used as a reference food. If bread was corrected with glucose as a reference food, the glycemic index of the ganyong-kelor snack bar was 38.08. The calculation of the glycemic load used the converted-glycemic index and the total carbohydrates contained in 100 grams of the food. Ganyong-kelor snack bar had a glycemic load value of 12.10.Conclusions: Ganyong-kelor snack bar had good nutritional content and was categorized as food with a low glycemic index. The hypoglycemic effect of the ganyong-kelor snack bar came from its high fiber content. Ganyong-kelor snack bar can be consumed as a healthy snack for diabetic people.